Universo simbólico da amamentação e da doação de leite humano: os sentidos atribuídos por mães doadoras do banco de leite humano da Maternidade Odete Valadares, Belo Horizonte, MG. - Maria Cristina Passos (2009)
The present study discusses the single meaning to breastfeeding and the donation of breast milk expressed in the discourse of mothers who donate breast milk. The mothers were selected in the human milk bank of the Maternity Odete Valadares, in Belo Horizonte. There were nine adult human milk donors who were willing to participate in the study. The content of the semi-structured interviews, conducted in the mothers’ houses, was recorded and transcribed in full. The theoretical saturation criterion was used to closure the group of participants. To guide the analysis process of the donors’ testimonies (deposition) some elements of discourse analysis were employed (MAINGUENEAU, 1997; CHARAUDEAU, 2001). The theoretical frame of reference for the transcribed and categorized material, originates from social and human sciences’ teories, taking into consideration the contributions of sociology, anthropology, psychology and other human sciences, in order to emphasize the symbolic dimension of the individuals (KLAUS E KENNEL, 1992; BADINTER, 1995; MAUSS, 2001; GODELIER, 2001; WINNICOTT, 2002; BOWLBY, 2002; VIGOTSKI, 2003). The analysis process of the donors’ discourse was built according to three main thematic axes: breastfeeding, donation, maternity. The discourses on breastfeeding reveal, in their majority, the mothers’ strong motivation and self-confidence that they would be able to produce good enough milk to sustain their children. Breastfeeding promotes feelings of closeness and satisfaction between the mother and child reinforcing the bonding between them. These feelings and sensations have developed since childhood when the mothers themselves were breastfed and they watched their mothers breastfeeding their brothers and sisters, not to mention, in some cases, other children, in the case of wet nurses. Regarding human milk donation, it can be said that mothers donate milk for various reasons such as: solidarity, altruism, retribution to received gift, excess of milk. The voluntary donation of human milk to unknown babies has the power of establishing milk bonds - milk brothers and sisters - increasing therefore, social relations. Both, breastfeeding and human milk donation are associated to the concept of “good mother”, the one dedicated and willing to do everything for her children.